2008
DOI: 10.1042/cs20070431
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peripheral and coronary function using laser Doppler imaging and transthoracic echocardiography

Abstract: Vascular dysfunction in the coronary and peripheral circulations is an early prognostic marker of future cardiovascular events. Measurements of coronary and peripheral vascular function in resistance vessels can be made, but rely on invasive procedures, which make them unsuitable for routine application. An assessment of the direct correlation between vascular responses in skin and coronary vessels has not been made previously. In 27 normal healthy subjects (18-55 years of age), we examined the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 32 publications
3
107
0
3
Order By: Relevance
“…Cutaneous blood flow responses to endotheliumdependent and -independent agonists were assessed using a laser Doppler multifiber probe (Perimed, Stockholm, Sweden) during transdermal iontophoresis of ACh and sodium nitroprusside (SNP), respectively, on the volar side of the forearm (16,34,39). The nondominant upper extremity was chosen in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Cutaneous blood flow responses to endotheliumdependent and -independent agonists were assessed using a laser Doppler multifiber probe (Perimed, Stockholm, Sweden) during transdermal iontophoresis of ACh and sodium nitroprusside (SNP), respectively, on the volar side of the forearm (16,34,39). The nondominant upper extremity was chosen in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…As such, these models provide a more integrative assessment of microvascular function as they elicit vascular responses that involve multiple-signaling pathways. Recent studies have indicated that changes in the cutaneous microvasculature often mirror changes in vessels of different size (Debbabi et al, 2010) and in other vascular beds, such as the coronary microcirculation (Khan et al, 2008). In fact, increasing evidence indicates that the cutaneous microcirculation can serve as a representative model to examine mechanisms of vascular function and dysfunction that occur on a systemic level (Holowatz et al, 2008;IJzerman et al, 2003).…”
Section: In Vitro Vascular Modelsmentioning
confidence: 99%
“…Cutaneous vasodilator function reflects generalized microvascular function since it can be used to interrogate endothelial vasodilator pathways (19). Cutaneous microvessel dysfunction correlates with coronary artery endothelial dysfunction (4,28,35) and is associated with several CVD risk factors, including obesity (13), hypertension (10,33), hypercholesterolemia (27), and type 2 diabetes (9, 37, 44), all of which frequently manifest in NAFLD patients (15). Nevertheless, the aforementioned studies utilized iontophoresis of acetylcholine to assay cutaneous vasodilator function, a technique that has accepted limitations since the delivery method is inconsistent and the vasodilator response is not exclusively NO mediated (20).…”
mentioning
confidence: 99%